Upgraded Business Model Integrating Agroecological Principles: Olive Growers’ in Elles Community, Northwest Tunisia - Dhehibi, Boubaker; Souissi, Asma; Dhraief, Mohamed Zied; Oueslati-Zlaoui, Meriem; Fendri, Mahdi; Ajmi, Larbi; Majri, Rihab; Frija, Aymen; Idoudi, Zied; M. Oumer, Ali; Ouji, Mourad; Ouerghemmi, Hassen; et al. (International Center for Agricultural Research in the Dry Areas, 2024)
The objective of this report is to investigate the prospects within local value chains by integrating agroecological principles into business models. The specific case study focuses on the olive oil value chain within the Elles community, situated in the Northwest region of Tunisia. An exhaustive analysis of pertinent stakeholders was conducted, complemented by the adaptation of a customized business model canvas tailored to the regional context. This investigation culminated in the identification of key insights and recommendations, leading to the development of an enhanced plan and a proposed framework for a novel business model with agroecological principles. Results showed that embedding agroecological principles within the business model will help upgrade this latter, fostering the transition towards agroecology. Transitioning to agroecology in Tunisia requires innovative financial mechanisms that align public policies, private sector investments, and farmer capacities to promote sustainable practices. The cost-benefit analysis of the investment projects associated with the upgraded business model integrating agroecological principles demonstrates their profitability based on key financial indicators such as the Internal Rate of Return (IRR) and Net Present Value (NPV). Sensitivity analysis reveals that the profitability of these projects could increase significantly under an optimistic scenario.